2005
DOI: 10.1111/j.1365-4632.2004.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of vitiligo to PUVA therapy in Saudi patients

Abstract: PUVA is still considered as the most appropriate and effective treatment for vitiligo. Saudi patients showed good response to treatment in general. Some sites such as the face, trunk, arms, and legs showed sensitivity to therapy, while hands, feet, and periorificial areas showed resistance to therapy. Generalized type was the best type to respond, followed by the periorificial type. Acral and segmental types were very resistant to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…Previously, it was reported that segmental vitiligo did not respond well to phototherapy 6,7 . We found that phototherapy was not helpful in the patients with segmental vitiligo who had the majority of white hairs in the lesional skin, supporting that melanocytes in the hair follicles play a role in repigmentation 8,9 .…”
Section: Clinical Data Of Nine Patientsmentioning
confidence: 58%
“…Previously, it was reported that segmental vitiligo did not respond well to phototherapy 6,7 . We found that phototherapy was not helpful in the patients with segmental vitiligo who had the majority of white hairs in the lesional skin, supporting that melanocytes in the hair follicles play a role in repigmentation 8,9 .…”
Section: Clinical Data Of Nine Patientsmentioning
confidence: 58%
“…In polygenic skin disorders, the proposed concept of isolated or superimposed segmental manifestation of polygenic skin disorders offers a reasonable explanation why: d mixed cases showing both segmental and nonsegmental involvement do occur (Tables I to III); d the segmental lesions tend to appear at a rather young age 29,31,32,42,44,46,58,[60][61][62][78][79][80][81][82][83] or may even be present at birth 11,12,20,84 ; d they often precede the appearance of nonsegmental lesions 8,13,21,34,37,38,55,56 ; d the segmental lesions tend to be rather pronounced (Tables I to III) 85 ; d the segmental lesions are extremely difficult to treat 27,45,86 ; and d family members may show the disorder in its nonsegmental form (Tables I and III). 78 On the other hand, in acquired, nonmendelian skin disorders the occurrence of a linear or otherwise segmental arrangement, with the exception of lesions representing a Koebner's effect, can be taken as heralding a polygenic predisposition.…”
Section: Resultsmentioning
confidence: 98%
“…Segmental vitiligo may be resistant to medical treatment. According to the previous reports, segmental vitiligo showed poor response to phototherapy such as PUVA and NBUVB (4, 5).…”
mentioning
confidence: 97%